The Influence of Discipline, Learning Facilities, and Friends Class to Economics Learning Outcomes - Hutanto, Muhamad Iqbal (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2021)
The research objective was to analyze the effect of discipline, learning facilities and peers on the economic learning outcomes of class XI students at SMAN 2 Probolinggo partially or simultaneously. This type of research uses a quantitative approach, a total sample of 97 students. Researchers used a questionnaire that was distributed to students. To ensure that the learning discipline influences, learning and peer facilities are really at the center of learning. The results of the study show that learning discipline, learning facilities and peers simultaneously have a positive effect and partially have a positive effect on learning outcomes. Through this research, it is able to explain student learning outcomes by 71.2%. The rest is influenced by variables outside the study.